¿De Christo con el alma mora, o de Mahoma con el bautismo de Christo ? Morisques et dissimulation : entre taqiyya et niyya - Youssef El Alaoui (Les Cahiers de Framespa)
The Moriscos were often accused of secretly practising the Muslim religion in accordance with a Koranic precept (Koran XVI, 106) ; it is called taqiyya or concealment. Widely disclosed by Louis Cardaillac (1977), this concept has been used indiscriminately by many researchers, leading to a dead end by denying the Moriscos, suspected of insincerity, any possibility of integrating or assimilating into old Christian society. We propose to take stock of recent work on the subject and to illustrate it with an analysis of the problem in certain works of Islamic refutation, particularly catechisms, as part of their evangelization.